2005
DOI: 10.1089/jop.2005.21.367
|View full text |Cite
|
Sign up to set email alerts
|

An Ex-Vivo, Whole-Globe Porcine Model of Corneoepithelial Wound Healing Tested Using Immunomodulatory Drugs

Abstract: Drug screening with this ex vivo porcine model permits a reproducibly quantitative and time- and dose-dependent assessment of corneoepithelial wound healing. This model corresponds more closely to the clinical situation than cell culturing and may, therefore, be useful in evaluating novel pharmaceutical agents, thereby helping to cut down on the number of animal experiments performed prior to the instigation of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…Flueckiger et al [51] reported that cyclosporine A (0.1-10 mg/ml) and dexamethasone (0.1-10 mg/ml) had no influence on corneoepithelial wound healing. Donshik et al [52] , using topical steroids in animals with moderate corneal ulcers, showed that steroids enhanced the severity of ulceration when given during the second and third week following the burn.…”
Section: Discussionmentioning
confidence: 99%
“…Flueckiger et al [51] reported that cyclosporine A (0.1-10 mg/ml) and dexamethasone (0.1-10 mg/ml) had no influence on corneoepithelial wound healing. Donshik et al [52] , using topical steroids in animals with moderate corneal ulcers, showed that steroids enhanced the severity of ulceration when given during the second and third week following the burn.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the corneas of the 2 species have comparable tensile strengths, 32 innervation pattern, 33 and anatomy. 34,35 In addition, the swine cornea has been used as a model for studying wound healing. 34 Thus, the porcine cornea was judged superior to the rabbit cornea as a model to evaluate the adhesives potential applicability to humans.…”
Section: In Vivo Application Of Adhesivementioning
confidence: 99%
“…34,35 In addition, the swine cornea has been used as a model for studying wound healing. 34 Thus, the porcine cornea was judged superior to the rabbit cornea as a model to evaluate the adhesives potential applicability to humans. A 6.0 mm trephine was used to create a trephination of the cornea to a midstromal depth.…”
Section: In Vivo Application Of Adhesivementioning
confidence: 99%
“…[32][33][34] Hence, the porcine eye is not an inappropriate choice of model to assess the impact of surgical technique and drug toxicity on corneal wound healing. 14,15,29,35,36 In our hands, the ex vivo whole-globe porcine model of corneoepithelial wound healing correlates well with clinical experience 14 and thus limits the need for experiments with living animals. Moreover, the setup permits a distinction between an inhibition of wound healing, which is indicated by a more tardy reduction in lesion size, and drug-induced toxicity per se, which is evinced by an enlargement of the primary lesion.…”
mentioning
confidence: 54%
“…Moreover, the setup permits a distinction between an inhibition of wound healing, which is indicated by a more tardy reduction in lesion size, and drug-induced toxicity per se, which is evinced by an enlargement of the primary lesion. 14 In conclusion, with the exceptions of cocaine 2.0% and lidocaine 2.0%, the topical anesthetic agents proved to be remarkably toxic at the tested concentrations (cocaine at 5.0% and 10.0%, procaine hydrochloride at 0.4%, and tetracaine at 0.5% and 1.0%). Ethanol, on the other hand, was well tolerated at all tested concentrations (2.0% to 99.0%).…”
mentioning
confidence: 76%